Fonoaudiologia educacional: percurso e percalços - Baptista, Ana Elisa de Belotti e Nogueira (2013)
This paper discusses the practices in Educational Fonoaudiologia* based on reflections on the course of the Educational Fonoaudiologia, its practices and inserts at the school staff and the removal of the clinical practice at schools. The questions brought here were raised during my practice in a private school in the city of São Paulo, where I worked as an educational fonoaudióloga*.Based on the discussions and reflections made in the course of this paper it was possible to think of possibilities and paths to make Educational Fonoaudiologia more effective in the educational space, trying to define / delimit their practices within the teaching team. The theoretical basis is the set of assumptions drawn by the Interactionism in Language Acquisition (De Lemos, 1992 and others), from the production literature developed since 1997 by researchers from LAEL-PUCSP. In this theoretical space, the discussions are heavily educated by European structuralism (SAUSSURE, 1916/1974; Jakobson, 1954; MILNER, 1978, 2002). Contributions from researchers in the field of speech pathology that turned to the historical path of the educational fonoaudiólogo were also included. The goal here was to discuss the role of the fonoaudiólogo in Education and thus, laws, opinions and guidelines that define the profile of this professional in Education, issued by the System of Federal and Regional Councils of Fonoaudiologia were examined. To spot what has been done by educational fonoaudiólogos working in this field, we conducted a qualitative study using questionnaire as the instrument with open and closed questions, answered by 5 educational fonoaudiólogos working in this area. The reports collected through these questionnaires were reported and analyzed in this paper. It is expected, therefore, to contribute to the characterization of reflection and practices in Educational Fonoaudiologia. *Speech, Voice , Oral-Motor and Hearing area of studies in Brazil ; fonoaudióloga is the professional graduated in these areas